Advantages of a New Low-Cost Negative Pressure Wound Therapy Using the "Turtle VAC": A Case Series. Issue 2 (April 2021) - Barau Dejean, J.M. Christina; Pean, J.T. Marc-Alain; Ottesen, Taylor D.; Woolley, Pierre Marie; Qudsi, Rameez A.; Dyer, George S.M.
Abstract : Case: We present a clinical case and technique guide demonstrating the use and effectiveness of a novel, low-cost negative pressure wound therapy (NPWT) device to achieve soft-tissue coverage in a 34-year-old patient with failed rotational flap and Masquelet technique on infected tibial nonunion. Local debridement was executed, NPWT initiated, and treatment culminated with complete wound healing. Conclusion: The "Turtle VAC" offers an effective low-cost alternative to commercially vacuum-assisted closure systems for post-traumatic wounds in low-resource setting of Haiti. Its use of available equipment makes NPWT accessible and can function as a bridge to definitive closure when primary wound closure is not possible and/or between debridement procedures.